2020
DOI: 10.1590/s0100-83582020380100024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Isoproturon With and Without Adjuvants on Photosynthetic Attributes of Wheat and Its Associated Weeds

Abstract: Among various weed management strategies, chemical weed control is considered the most effective method. However, optimum dose and suitable combination of herbicide with adjuvants play a vital role in controlling weeds at an acceptable level and produce maximum crop yield. A field study was conducted to investigate the effect of post-emergence herbicide isoproturon alone or with combination of adjuvants on winter wheat and its associated weeds. The treatments were isoproturon at 175 g a.i. ha-1, 140 g a.i. ha-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…These fallouts are in promise with the findings by Bibi et al (2008) who exposed that herbicides have substantial impacts on wheat of 1,000-grain weight. Similarly, Javaid et al (2020) also stated that when isoproturon was applied as a foliar spray, the highest biological yield was obtained. Hamouda et al (2021) concluded that the addition of Argal or Techno oil to herbicides spray solutions at reduced rates, especially at three-fourths of the recommended rate resulted in enhancing the herbicidal activity against weeds and increasing wheat grain yield.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…These fallouts are in promise with the findings by Bibi et al (2008) who exposed that herbicides have substantial impacts on wheat of 1,000-grain weight. Similarly, Javaid et al (2020) also stated that when isoproturon was applied as a foliar spray, the highest biological yield was obtained. Hamouda et al (2021) concluded that the addition of Argal or Techno oil to herbicides spray solutions at reduced rates, especially at three-fourths of the recommended rate resulted in enhancing the herbicidal activity against weeds and increasing wheat grain yield.…”
Section: Discussionmentioning
confidence: 97%
“…Phalaris minor , M. indica , F. indica , and A. arvensis are weeds of winter wheat and cause a severe reduction in wheat yield if not controlled at the appropriate stage ( Abbas et al, 2018b ; Javaid et al, 2020 ). However, an effective dose, optimum time, and suitable mixture of herbicide along with adjuvants is required to suppress the weed growth and enhance wheat yield ( Javaid and Tanveer, 2013 ; Safdar et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations